2023
DOI: 10.1055/s-0043-1768450
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Pediatric Surgical Scientific Formats: An ERNICA Survey on Challenges and Future Directions

Abstract: Introduction The aims of this survey were to assess the experiences of the transition from in-person to virtual meetings among European pediatric surgeons since the beginning of the coronavirus disease 2019 (COVID-19) pandemic and to identify preferences for future formats. Materials and Methods An online questionnaire was circulated among members of the European Reference Network for rare Inherited and Congenital Anomalies Network (ERNICA) in 2022. Two time periods were compared (3 years before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…McClintic and Stashevsky do not attempt to measure what could be lost with virtual meeting formats, such as opportunities for networking, career development, collegial interactions, idea sharing, and so on, but these are important aspects of medical conferences that cannot be ignored. Aubert et al distributed an online questionnaire to a group of European pediatric surgeons to evaluate their perspectives after transitioning to virtual meeting formats. Most respondents found virtual meetings to be more economical (82%) and practical (78%); however, a similar-sized majority indicated that they missed the social aspect of in-person meetings (78%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…McClintic and Stashevsky do not attempt to measure what could be lost with virtual meeting formats, such as opportunities for networking, career development, collegial interactions, idea sharing, and so on, but these are important aspects of medical conferences that cannot be ignored. Aubert et al distributed an online questionnaire to a group of European pediatric surgeons to evaluate their perspectives after transitioning to virtual meeting formats. Most respondents found virtual meetings to be more economical (82%) and practical (78%); however, a similar-sized majority indicated that they missed the social aspect of in-person meetings (78%).…”
mentioning
confidence: 99%
“…Most respondents found virtual meetings to be more economical (82%) and practical (78%); however, a similar-sized majority indicated that they missed the social aspect of in-person meetings (78%). Of note, 62% of respondents had a preference for a hybrid format for future meetings . This illustrates that there are several directions in which existing research on this topic can and perhaps should be expanded in the future.…”
mentioning
confidence: 99%